(3QSGdI aj ebGd GdbGFdjf HGdMGd ef CUMGHfG hCUMGH GdGYJRGds - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdeJYGd Pi GdLdGd hGdLeGd hHYO agPg QSGdI eQJHI ai ebGd GdbGFdjf HGdMGd ef CUMGHfG hCUMGH GdCYJRGd hbO GaUM Yf gPG fUQ GdWhSi ai JdNjU GdeMUd s
(3BNQgG (B:s
(3Efg jdRe UMI GdJMdjd ai LejY GdUhQ MJi jdRe ai gPg GdUhQ KHhJ GdTF dfaSg adjS TF GPgi jfgOe CSGS GdCSJOGd GdePchQ ceG dGjNai Ydi ef dg COfi JCed JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds